COVID-associated left atrial changes as a significant predictor of atrial fibrillation recurrence - An. M. Osadchiy; V. V. Semenyuta; A. V. Kamenev; A. Yu. Anisenkova; S. G. Shcherbak; D. S. Lebedev (Российский кардиологический журнал)
Aim. To determine the prognostic significance of left atrial (LA) changes after SARS-CoV-2 infection on the atrial fibrillation recurrence rate after catheter ablation.Material and methods. The study involved 40 patients. All patients were monitored after 3, 6 and 12 months, as well as when the clinical performance of the disease changed. The average follow-up time was 19±3 months. Recurrence of atrial fibrillation was observed in 18 patients (45%).Results. The study groups were completely comparable in age (p=0,382), sex (p=0,604), arrhythmia type (p=0,842), and history of previous surgeries (p=0,949). Arrhythmia recurrence was 9,33 [2,18; 39,96] times more common in patients who had SARS-CoV-2 infection before surgery (p=0,01). Arrhythmia recurrence after catheter ablation caused by left atrial posterior wall fibrosis and without pulmonary vein reconnection is an independent risk factor for recurrence after another ablation attempt (p=0,020). Also, arrhythmia recurrence was 9 [2,09; 38,79] times more common in patients after left atrium posterior wall box isolation (p=0,002). About half of the atrial area in patients with arrhythmia recurrence is represented by myocardium with an amplitude of less than 0,25 mV. In patients without recurrence, the area with this amplitude is on average 15,9% smaller (49±18,4% and 33,1±17,5%, respectively; p=0,020). Differences in the myocardial area with an amplitude of less than 0,5 mV are more pronounced and average 21,4% (p=0,006). LA myocardial tissue with normal signal amplitude (>0,75 mV) is represented by only 17,4% of the area in patients with disease recurrence, which is 2,14 times less than in patients with remission (p=0,011).Conclusion. LA myocardial changes after SARS-CoV-2 infection are stable over time and significantly increase the arrhythmia recurrence risk after catheter ablation. Additional left atrial posterior wall box isolation does not reduce the risk of recurrence and does not significantly affect the duration of sinus rhythm control.